Prescribed psychotropic medication patterns among treated Foster Care enrollees: a single institution study - Cosme, Celica Glenn; Rudig, Nathan O.; Borsellino, Philip J.; Chea, Deanna; Krider, Reese I.; Durette, Lisa (Frontiers in Psychiatry, 2024)
Background: Studies show foster care involved youth are more likely prescribed psychotropic medications and polypharmacy, these patterns have not been explored in the state of Nevada. Methods: Data from a single institution's EHR analyzed the prevalence of psychotropic prescribing and polypharmacy in children ages 2 to 19 between July 2019 to June 2022. Results: Of 569 distinct psychotropic medication prescriptions, the most frequent psychotropic classes were non-stimulant ADHD medications (alpha-agonists and atomoxetine, 31.5%), atypical antipsychotics (22.1%), antidepressants (20.6%), and stimulants (16.0%). Stimulants and non-stimulant ADHD prescriptions decreased in older age groups while antidepressants and antipsychotics increased in older age groups. During the period studied, 24% of psychotropic prescriptions increased in dosage. In children prescribed with psychotropic medications, concomitant medication use for at least 60 days occurred in 28% of children who had any psychotropic medication prescribed. Conclusion: Within our cohort, non-stimulant ADHD medications (both alpha-agonists and atomoxetine) and atypical antipsychotics were more commonly co-prescribed additional psychotropic medication compared to other co-prescribed medication categories. This study illustrates prescribing patterns in a community mental health clinic focused on judicious prescribing of psychotropic medications in foster care enrolled youth. Despite this, 41% of the youth treated in this clinic received at least one prescription for psychotropic medication, and of those, 27.8% were prescribed more than one psychotropic medication at the same time. More studies are necessary to understand the underlying causes of high prevalence of concomitant medication use and prescribing practices of psychotropic medications use in foster care involved pediatric populations.